2018
DOI: 10.1155/2018/1546075
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of Subcutaneous Fat Is a Predictive Factor of Incisional Surgical Site Infection in Crohn’s Disease Surgery: A Retrospective Study

Abstract: Background Incisional surgical site infection (iSSI) is a frequent postoperative complication of abdominal surgeries in patients with Crohn's disease (CD). In this study, we investigated the association between thickness of subcutaneous fat (TSF) and iSSI in patients with CD undergoing intestinal resections. Patients and Methods Patients with CD who had undergone abdominal surgery from January 2014 to January 2017 were included in this retrospective study. Patients' TSF and other possible predictors of iSSI, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…Second, we found that TSF is a predictor for incisional SSI in patients undergoing open appendectomy. This finding confirms what other studies have shown that TSF was independently associated with SSI in a variety of surgical procedures, including Crohn's disease surgery, elective colorectal surgery, abdominal hysterectomy, and cervical spine fusion surgery [14,15,24,25]. In our study, BMI was shown to be linearly related with TSF as evidenced by multicollinearity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Second, we found that TSF is a predictor for incisional SSI in patients undergoing open appendectomy. This finding confirms what other studies have shown that TSF was independently associated with SSI in a variety of surgical procedures, including Crohn's disease surgery, elective colorectal surgery, abdominal hysterectomy, and cervical spine fusion surgery [14,15,24,25]. In our study, BMI was shown to be linearly related with TSF as evidenced by multicollinearity.…”
Section: Discussionsupporting
confidence: 92%
“…However, other study has reported a markedly lower cut-off TSF value of 10.2 mm for patients undergoing Crohn's disease surgery [14]. This difference can be explained as Crohn's disease is a type of wasting disease and thus differs from other diseases [14]. This highlights the need for a differential cut-off value for TSF depending on diseases involved.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations